The contest effectiveness of the men's National Judo Team of Japan, and character of their technical-tactical preparation during the World Judo Championships 2010 - Adam, M.; Tyszkowski, S.; Smaruj, M. (Baltic Journal of Health and Physical Activity, 2011)
Background: The aim of our research was to determine the contest effectiveness of Japanese judo competitors and to state the quantitative an qualitative indices of the tactical-technical preparation (PTT). The values of these indices may be used for controlling the process of special preparation.